Lung Pathology - Houser, Stuart. (Current Clinical Pathology,, 2005)
Learning the diagnostic elements of lung pathology requires not only great familiarity with a wide diversity of cases, but also a sharp eye for analyzing pictorial images. In Lung Pathology: A Consultative Atlas, leading experts offer a novel and substantive approach to the teaching of pulmonary pathology. Drawing on 263 challenging, yet exemplary, referral cases taken from files collected over 20 years by internationally renowned lung pathologist, Dr. Eugene Mark, the authors introduce his state-of-the-art approach to the interpretation of pulmonary pathology. This text includes the primary and/or differential diagnosis and the pertinent histological features of each case, as well as clinical history, when available. Key words or phrases in the text are highlighted and digitally hyperlinked to associated images or regions of interest within those images to assist the readers in their correlation. Novel and user friendly, Lung Pathology: A Consultative Atlas describes a cutting-edge diagnostic approach to pulmonary pathology, describing its principles and demonstrating its application in text and full-color illustrations drawn from 263 difficult cases of human lung pathologies.